Current situation and influencing factors of knowledge, attitude and practice of excessive oxygen therapy among medical staff in the Department of Respiratory and Critical Care Medicine (呼吸与危重症医护人员过度氧疗知信行现状及影响因素分析) - YU Xiaona (于小娜); WANG Fen (王芬); TAN Rong (谭荣); CAI Bei (蔡贝) (中西医结合护理, 2024)
Objective To investigate the current situation of knowledge, attitude and practice of excessive oxygen therapy among medical staff in the Department of Respiratory and Critical Care Medicine. Methods Questionnaire on the use of excessive oxygen therapy for medical staff in respiratory and critical was used to investigate 734 medical staff of respiratory and critical care department in more than 40 secondary and higher-level hospitals in 11 provinces and cities. Results The total score of knowledge and practice of excessive oxygen therapy among medical staff in the Department of Respiratory and Critical Care Medicine was (134. 97+-17. 75). The scores of knowledge, attitude and behavior were (29. 08+-4. 58) points, (43. 30+-5. 48) points and (62. 59+-7. 69) points respectively. Multiple linear regression analysis showed that the main influencing factors of the knowledge, attitude and practice of excessive oxygen therapy for medical staff in respiratory and critical care department were whether they had learned the guidelines and literatures of excessive oxygen therapy in the past 12 months, academic background, professional title, hospital grade, and active involvement in oxygen therapy (P<0. 05). The knowledge, attitude and behavior of medical staff in respiratory and critical care department were at a moderate level. Conclusion Medical staff in the Department of Respiratory and Critical Care Medicine should strengthen the knowledge learning and training of excessive oxygen therapy, make full use of the advantages of high education and professional titles to play a guiding and driving role, change the learning attitude, reduce the incidence of excessive oxygen therapy in patients, and improve the safety and effectiveness of oxygen therapy in patients in the Department of Respiratory and Critical Care Medicine. (目的 了解呼吸与危重症医学科医护人员过度氧疗知信行的现状, 分析其影响因素。方法 采用呼吸与危重症医学科医护人员过度氧疗知行问卷, 对我国11个省市40多所二级以上综合医院的734名呼吸与危重症医学科医护人员进行问卷调查。结果 呼吸与危重症医学科医护人员过度氧疗知信行总分为(134. 97+-17. 75)分。知识、态度、行为维度得分分别为(29. 08+-7. 69)分。多元线性回归分析显示, 呼吸与危重症医学科医护人员过度氧疗知信行的主要影响因素为近12个月是否学习过氧疗指南及文献、学历、职称、医院等级、主动积累氧疗相关知识(P＜0. 05), 呼吸与危重症医学科医护人员对过度氧疗知识、态度、行为水平均处于中等水平。结论 呼吸与危重症医学科医务人员应加强过度氧疗相关知识学习与培训, 充分利用高学历、高职称的优势来发挥指导和带动作用, 转变学习态度, 减少患者过度氧疗发生率, 提高呼吸与危重症医学科患者氧疗安全性及有效性。)